A peculiar behaviour for cell death induced by weak carboxylic acids in the wine spoilage yeast Zygosaccharomyces bailii - Estevinho, Leticia M. (2011)
In glucose-grown cells of Zygosaccharomyces bailii, ISA 1307 acetic acid and other carboxylic acids enhanced death. The effects were much lower than those described for Saccharomyces cerevisiae, being only detectable at higher acid concentrations. In Z. bailii, acetic acid and other weak acids also induced intracellular acidification, but this effect was less pronounced than that of death and no relationship was found with death enhancement. The results suggested that in Z. bailii, unlike S. cerevisiae, intracellular acidification induced by weak acids is less pronounced and appears not to have a significant role in death at the temperature range used.